(untitled) (International Journal of Scientific Pediatrics, 2023)
Annotation. This scientific study is devoted to the study of autonomic dysfunction syndrome (АVD), which is most often formed in adolescents. The results of the analysis of outpatient records of children are presented, the frequency of occurrence is determined and risk factors for АVD in students of secondary specialized educational institutions are identified. The purpose of the study: is to study the frequency of occurrence and identify risk factors for the development of autonomic dysfunction in puberty children. Materials and methods: To study the frequency of occurrence and identify risk factors for the development of autonomic dysfunction syndrome, 100 adolescents enrolled in secondary specialized educational institutions aged 12-17 years were examined. A prerequisite was the informed consent of the teenager or parents to participate in the study. The study was conducted in the form of a questionnaire and a survey algorithm was created. Questionnaire forms with the identified factors were filled out for all examined adolescents. Results and discussions According to the survey data, it was revealed that the greatest factors of the development of АVD in children aged 12-15 years are mental fatigue (50%), hormonal imbalance, pre- and puberty (44%), stress during pregnancy (41%), etc. Therefore, taking into account the established risk factors, it is possible to predict the development of АVD in children, especially with burdened obstetric pathologies and hereditary factors. Conclusion. The problem of АVD in children and adolescents is relevant not only for pediatricians and pediatric cardiologists but also for doctors of other medical specialties: therapists, neurologists, psychotherapists, and endocrinologists. The syndrome of autonomic dysfunction (АVD) and its manifestations in children still cause a large number of questions to which there are the same set of answers, and not always unambiguous.